The Impact of Socio‐Political Cleavages on Constitutional Referendums: The Case of Chile 2022 - Mauricio Morales; Teresa Pérez‐Cosgaya (Politics and Governance)
A constitutional referendum was held in Chile in 2022. The competing options were to “approve” or “reject” the proposed new constitution written by a Constitutional Convention, as the “reject” option triumphed, the 1980 constitution remained in force. This study identifies the basis of support for the winning option. To do so, we draw on the theory of sociopolitical cleavages. Specifically, we measure the effect of the religious division in force since the mid-19th century, the urban social class division of the early 20th century, the urban/rural division of the mid-20th century, and the authoritarianism/democracy division resulting from the dictatorship of General Pinochet (1973–1990). Based on an analysis of electoral data in Chile’s 345 municipalities and a survey of 2,117 people taken before the referendum, we conclude the following: First, “reject” was the strongest among evangelical voters. Second, while “reject” performed better in the country’s poorest municipalities, in the Metropolitan Region, which accounts for 40% of the population, the result was the opposite. Third, “reject” performed better in municipalities with a higher percentage of rural population. Fourth, “reject” was the preferred option for voters who were more inclined toward authoritarian rule. Consequently, while constitutional referendums can be explained by support for incumbents—in this case, for the president of the republic, who supported the Convention’s constitutional proposal—this does not imply that sociopolitical cleavages are irrelevant. This study shows that even though a referendum may respond to short-term variables, such as low presidential approval, sociopolitical cleavages still robustly explain electoral outcomes.